Meta-Analysis of Scientific Studies About Port-Hinterland Relations - Melika Zarei; Mojtaba Arasteh; Khalil Hajipour (جغرافیا و آمایش شهری منطقه‌ای, 2023)
Regional transportation, especially between port-hinterland, plays an important role in the economic prosperity of the country and the efficiency of the supply chain of commudities. Due to the functional and geographical differences between the hinterlands, the impact of the performance of each port on the post-coastal regional development is different leading to the diversity of different types of spatial structure in the port areas. Due to this fact, many researchers who are working in various scientific fields focus on the analyzing the relations between ports and hinterland areas and explaining the changes occurred in the spatial structure of these areas. The purpose of this research is to systematic review of researches in this field and to classify the structure and content analysis of prominent articles during period of 1997 to 2022. All of articles downloaded from Scopus database and analyzed by VOSviewer software. A comparison of the results of this research shows that in terms of specialization and distribution of journals, “The Journal of Transport Geography” is one of the main attractive journals for the researchers of spatial geography of ports. In terms of the geographical scale of the studies, most of the researches in this field have investigated the spatial structure of port-hinterland as a national scale. In addition, the geographical areas are mostly focused on the East and Southeast Asia.In terms of spatial structure typology, two types of analysis have been proposed and used in the selected articles. The first type is morphological analysis of the port-hinterland structure. The components used in this type of analysis include the objective components of the spatial structure (center, corridor, and land use area); the second type is the functional analysis of the port-hinterland structure, in which it often includes the intangible components of space (interaction, regularity and spatial territory). The results of this research show that the set of theories of port-hinterlandcan be summarized in seven thematic axes: Relations between the hinterland, port and foreland; Regional development of ports; Dry and inland ports; Port-city interface; Connections between ports and corridors; Competition between ports and forelands; and Function of ports. Finally, by reviewing the methods and techniques used in the articles, we can find four approaches of positivism, neo-positivism, relationalism and criticism in the philosophical-historical evolution of the port-hinterlamd articles.